2015
DOI: 10.1002/j.0022-0337.2015.79.4.tb05894.x
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Dependence Education in U.S. Dental Assisting Programs’ Curricula

Abstract: The aim of this study was to assess the level of tobacco dependence education (TDE) in the curricula of U.S. dental assisting programs and to compare the indings to those from a similar assessment of dental hygiene curricula. In the 2012-13 academic year, a 51-item survey was sent to directors of all 298 accredited dental assisting programs. Assessed were curricular TDE content, time spent on each topic, expected levels of clinical competence, and resources used. Of the 298 potential participants, 89 programs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Adequate modifications in the dental education curriculum was recommended to improving dentist's involvement in smoking cessation [23]. Education and are needed for dentists to develop their knowledge and abilities [17,19] and foster positive attitudes toward tobacco cessation counseling (TCC) [24][25][26]. Most dental students are aware that TCC is within the scope of dentist services.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate modifications in the dental education curriculum was recommended to improving dentist's involvement in smoking cessation [23]. Education and are needed for dentists to develop their knowledge and abilities [17,19] and foster positive attitudes toward tobacco cessation counseling (TCC) [24][25][26]. Most dental students are aware that TCC is within the scope of dentist services.…”
Section: Introductionmentioning
confidence: 99%
“…These reported barriers are not unique to this study as it has been previously reported that the barriers that preclude dentists and dental hygienists from incorporating tobacco cessation into practice include self-doubt about their knowledge and skills in assisting patients as well as self-doubt about their effectiveness to give quitting advice. [ 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that although most of the dentists have an encouraging attitude in taking responsibility for smoking cessation, their involvement in cessation counseling is limited, with other reports of an overall feeling of doubt among general dentists about the effectiveness of their smoking cessation advice and lack of confidence. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%